Poverty in a Wealthy Economy : The Case of Nigeria - Canagarajah, Sudharshan; Thomas, Saji. (Washington, D.C. : International Monetary Fund, 2002)
This paper describes the nature and evolution of poverty in Nigeria between 1985 and 1992. It highlights the potential wealth of the Nigerian economy and examines how the economic policies pursued in the 1980s and 1990s impacted economic growth and welfare. The headcount measure of poverty in Nigeria declined from 43 percent to 34 percent between 1985 and 1992. Decomposing the factors causing the reduction in poverty shows that the overall decline of 9 percentage point was the net result of a 14 percentage point decline owing to the growth factor and a 5 percentage point increase owing to the income distribution factor. The paper proposes that promoting broad-based growth and targeted interventions in health, education, and infrastructure need to be central strategies in the fight against poverty in Nigeria.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet